Unreliable Narration in Law and Fiction - Del Gobbo, Daniel (2017)
This article revisits long-standing debates about objective interpretation in the common law system by focusing on a crime novel by Agatha Christie and judicial opinion by the Ontario High Court. Conventions of the crime fiction and judicial opinion genres inform readers’ assumption that the two texts are objectively interpretable. This article challenges this assumption by demonstrating that unreliable narration is often, if not always, a feature of written communication. Judges, like crime fiction writers, are storytellers. While these authors might intend for their stories to be read in certain ways, the potential for interpretive disconnect between unreliable narrators and readers means there can be no essential quality that marks a literary or legal text’s meaning as objective. Taken to heart, this demands that judges try to narrate their decisions more reliably so that readers are able to interpret the texts correctly when it matters most.
Keywords: Daniel Del Gobbo